2016
DOI: 10.1242/jcs.183590
|View full text |Cite
|
Sign up to set email alerts
|

Targeting surface voids to counter membrane disorders in lipointoxication-related diseases

Abstract: Saturated fatty acids (SFA), which are abundant in the so-called western diet, have been shown to efficiently incorporate within membrane phospholipids and therefore impact on organelle integrity and function in many cell types. In the present study, we have developed a yeast-based two-step assay and a virtual screening strategy to identify new drugs able to counter SFA-mediated lipointoxication. The compounds identified here were effective in relieving lipointoxication in mammalian β-cells, one of the main ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In previous work (7,13,15,28), the error on p was determined from the error on the linear fit of the logarithmic plot, thus considering the logarithmic value of p(A). However, we believe that an error determined by block averaging, as reported here, is more reliable, and we encourage the users to follow this procedure in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work (7,13,15,28), the error on p was determined from the error on the linear fit of the logarithmic plot, thus considering the logarithmic value of p(A). However, we believe that an error determined by block averaging, as reported here, is more reliable, and we encourage the users to follow this procedure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently developed a computational approach to identify lipid-packing defects based on mapping of the membrane surface according to a Cartesian grid. This method has allowed us to investigate the effect of various membrane parameters on interfacial properties, including acyl chain mono-and polyunsaturation (8,13,14), membrane curvature (7), and the presence of conical lipids or of molecules against lipointoxication (15). The pivotal role of interfacial voids has been suggested by a number of recent investigations on disparate topics, including membrane remodeling processes such as bending, fusion, and fission (8,(16)(17)(18)(19) as well as the binding of peripheral proteins, disaccharides, and nanoparticles (8,14,20).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the UPR is activated upon SFA overload, in virtually all cell types, including, among others, pancreatic b-cells [63][64][65], hepatocytes [66], muscle cells [67], adipocytes [68], yeast [69], and, relevant to the present review, bronchial epithelial cells [17,18].…”
Section: Lipointoxication and The Er Function: The Er Stressmentioning
confidence: 99%